Analisis Penyakit Gigi Molar dengan Menggunakan Metode Forward Chaining - Khairul Fajri Ilahi (SEULANGA SYSTEM PUBLISHER, 2023)
Molar teeth or what are often referred to as molars are the teeth that are most often used in the process of digesting food before it enters the stomach. This also makes molar teeth one of the most common diseases suffered by the community. This is also accompanied by low public knowledge about molar teeth. The number of people who suffer from molar tooth disease is not proportional to the availability of dental experts, causing all patients who want to diagnose their disease to be unserved. The method used in this research is the Forward Chaining method. The purpose of this study was to test the Forward Chaining method in analyzing molar disease and provide an initial diagnosis of molar disease so that the diagnosis generated by the system can be used as a reference for consultation with a dentist. The data used in this study were data on symptoms and diseases of molar teeth taken from the Munggu Dental Care dental clinic, the data obtained in the form of 29 symptom data and 7 data on molar tooth disease. The data obtained is then processed using the Forward Chaining inference method or search from the front. Then the patient will be asked to choose the symptoms they feel and the system will diagnose the patient's disease based on the symptoms entered by the patient. The data that enters the system will then be matched with the existing rules in the database so that an initial diagnosis will be generated. The result of this research is the Forward Chaining method designed with the PHP programming language using the Codeigniter framework is able to analyze diseases of the molar teeth very accurately. Therefore, this research can be used as a reference for further research and the resulting expert system can be used by users who want to diagnose molar tooth disease before going to the dentist